1977
DOI: 10.1002/bjs.1800640521
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of graduated compression stockings in the prevention of deep vein thrombosis

Abstract: The incidence of deep venous thrombosis (DVT) was studied by the 125I-fibrinogen technique in 70 patients who had had major abdominal operations and who were wearing graduated static compression stockings on one leg, the patient's other leg being used as a control. In the whole group 7 patients developed bilateral DVT, 19 patients developed unilateral DVT in the control leg and only one patient developed unilateral DVT in the stockinged leg. The difference between stockinged and control legs was highly signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(31 citation statements)
references
References 17 publications
2
26
0
3
Order By: Relevance
“…Eight RCTs compared GCSs alone with no stockings; the incidence of DVT was statistically significantly lower in the stocking group than in the no stockings group. [22][23][24][25][26][27][28][29] Ten RCTs compared GCSs plus another prophylactic method versus the prophylactic method alone; the incidence of DVT was statistically significantly lower in the stocking plus other prophylactic method group than in the other prophylactic alone group. [30][31][32][33][34][35][36][37][38][39] The authors concluded that GCSs are effective at diminishing the risk of DVT in hospitalised patients.…”
Section: Cochrane Review: Elastic Compression Stockings For Preventiomentioning
confidence: 99%
“…Eight RCTs compared GCSs alone with no stockings; the incidence of DVT was statistically significantly lower in the stocking group than in the no stockings group. [22][23][24][25][26][27][28][29] Ten RCTs compared GCSs plus another prophylactic method versus the prophylactic method alone; the incidence of DVT was statistically significantly lower in the stocking plus other prophylactic method group than in the other prophylactic alone group. [30][31][32][33][34][35][36][37][38][39] The authors concluded that GCSs are effective at diminishing the risk of DVT in hospitalised patients.…”
Section: Cochrane Review: Elastic Compression Stockings For Preventiomentioning
confidence: 99%
“…A postal survey of orthopaedic surgeons in the UK showed that 68% used graded compression stockings as prophylaxis for DVT (Laverick, Croal and Mollan 1991). Their efficacy has been well documented in abdominal surgery (Holford 1976;Scurr et al 1977;Allan et al 1983;Turner, Cole and Brooks 1984;Wille-Jorgensen et al 1985;Jeffery and Nicolaides 1990), but there is little information on their use in orthopaedic surgery (Barnes et al 1978;Ishak and Morley 1981;Ohlund, Fransson and Starck 1983).…”
Section: Graded Compression Stockings For Prevention Of Deep-vein Thrmentioning
confidence: 99%
“…The general application of two non-specific and rather insensitive methods for DVT and AD exclusion by the combination of a negative SimpliRed (Simplify) and low clinical score should be estimated as not safe enough mainly because the prevalence of DVT in the low clinical score group may vary widely (3% to 12%) [48,65]. According to our experiences and analysis of literature findings [48,73] the safest and most effective and sensitive approach for DVT and AD exclusion is to start with objective testing with CCUS, followed by a qualitative or less sensitive D-dimer test without the use or need of clinical score assessment (Figures 4 and 7). A first negative CCUS and a negative ELISA VIDAS test (<500 ug/mL) excludes DVT irrespective of clinical score assessment (left arm, Figure 7).…”
Section: Ccus D-dimer and Clinical Score Strategy To Rule In And Outmentioning
confidence: 99%
“…In acute DVT patients (21,41,73,74 MECS may also be used for symptomaticrelief of swollen acute DVT legs combined with low-molecular weight heparins (LMWH) followed by vitamin K antogonists (VKA) or novel oral anticoagulants (NOACs). Pneumatic compression therapy has been proved to be effective, but is probably only realistic in post-operative circumstances, and it has shown to be effective in for example elective knee or hip replacement [21,41,74].…”
Section: Management Of Dvt In the Primary Care And Hospital Settingmentioning
confidence: 99%